KOMPETENSI DAN PERSPEKTIF FEMININ DALAM AUDIT - Karnawati, Yosevin - (Jurnal Ekonomi : Journal of Economic, 2020)
Audit quality is all posibilities (auditor) where the auditor when auditing the financial statements can find what is happening in the clientâ€™s accounting system and report it in audited financial statements. The audit must be carried out by one or more people who have sufficient expertise and technical training. The gender factor is an individual characteristic that is brought for within a person that is brought along and self perception is related to the way in which information is collected and prepared, thus affecting the quality of the resulting audit. This study tries to analyze competence and associate gender with audit quality.The subject in this study were auditors who worked at Kantor Akuntan Publik (KAP) in West Jakarta. Data collections uses purposive sampling with the criteria of auditors who have worked at least one years in KAP. The design of this study is causality or causation, using multiple linier regression analysis tools.The result showed that audit knowledge has a positive affect on audit quality but feminine personality negatively affects audit quality. While work experience and masculine personality has no effect to audit quality. This research to produces audit quality that is produced from audit knowledge while audit knowledge will increase accountability so that it will improve the quality of work results. On the other hand aggressive, emotional and illogical attitudes possessed by feminine personalities would otherwise lose audit quality.Â Keywords: audit knowledge, work experience, gender, feminine, masculine, audit quality